MODEL PENGEMBANGAN USAHA PERIKANAN TANGKAP DI DAERAH ISTIMEWA YOGYAKARTA - Mulyono Partosuwirjo; John Haluan; Mulyono S. Baskoro; Soepanto Soemokaryo (Jurnal Manajemen & Agribisnis, 2008)
Capture fishery has an important role in the economic activity and livelihood among the people ofYogyakarta, but its dynamic interaction is not yet effective and still dominated by monopoly practices.This study has analyzed the feasibility and appropriate dynamic interaction for the development ofcapture fishing. The method developed in the study consisted of a cost-benefit analysis and SEM.Catching fish using sero, payang, gillnet, and krendet was found to be feasible and obtain net profits of Rp. 44,291,851, Rp. 91,202,416, Rp 47,585,387, and Rp 56,514,757, respectively. The most significant aspects of interaction determining the environments (internal, external, and industrial), business strategies, fishing industry performance, and development goals were management, social aspect, entry barrier, finance, and feedback period. For the construct interaction, the internal environment had a significant positive effect on the external environment, the external environment had a significant positive effect the industrial environment, and the business strategies had a significant positive effect on the goal of fishery development.